(untitled) (Manila, 1965)
The documents in this lolume were written by the actors of that great drama of conquest and Christianization. Contents: letter from Philip II to Luis de Velasco, Letter from Philip II to Andres de Urdaneta, ...
Keywords: Philippines,Philippines; History,Lịch sử; 1521-1812